2008
DOI: 10.1177/026010600801900305
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Change of Lipid and Fatty Acid Composition of Little Tuna Euthynnus Alletteratus-By-Prodvcts

Abstract: Little tuna (Euthynnus alletteratus) is an important Mediterranean commercial fish species. In this study, the lipids of tuna filet, head, viscera, liver, and gonads fished in Tunisian waters were examined in summer and winter. Total lipid content in most organs showed a significant variation due to seasonal change. The highest lipid content was found in head in little tuna fished in winter and summer (14.2%). The lowest levels were attributed to gonads (1.5%). The major fatty acids classes were polyunsaturate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 7 publications
2
14
0
Order By: Relevance
“…The percentage of total muscle tissue (red and white muscle) reported in Table 5 was comparable to the reported value of 60% (Graham et al, 1983), and the percentage of fat found in the head is comparable to previously published data (Nguyen et al, 2012;Selmi et al, 2008) with values ranging from 12% to 14%. However, Nakamura et al (2007) performed proximate analysis of wild and cultured Pacific bluefin (average mass = 33 kg) and reported lipid contents in the musculature that were substantially higher than those found in this study.…”
Section: Discussionsupporting
confidence: 90%
“…The percentage of total muscle tissue (red and white muscle) reported in Table 5 was comparable to the reported value of 60% (Graham et al, 1983), and the percentage of fat found in the head is comparable to previously published data (Nguyen et al, 2012;Selmi et al, 2008) with values ranging from 12% to 14%. However, Nakamura et al (2007) performed proximate analysis of wild and cultured Pacific bluefin (average mass = 33 kg) and reported lipid contents in the musculature that were substantially higher than those found in this study.…”
Section: Discussionsupporting
confidence: 90%
“…This study demonstrates temporal variations in feeding conditions between and among adult forage fishes collected from the NW Mediterranean Sea in summer (July 2010) Selmi et al 2008) and are linked to regionally specific trophic dynamics, particularly food supply (quality and quantity), which dictate the nutritional condition of consumers.…”
Section: Lipids Infer Temporal and Basin-wide Variations In Local Feementioning
confidence: 84%
“…The fish heads and trimming resulting from processing were employed for oil production from Alaskan processed seafood (Oliveira & Bechtel 2005) and tuna fish (Chantachum et al 2000;Selmi et al 2008). In particular, fish head and liver have long been a source of fish oil and consumed to improve vision and growth (Selmi et al 2008).…”
Section: Tbp Physico-chemical Characterizationmentioning
confidence: 99%
“…In particular, fish head and liver have long been a source of fish oil and consumed to improve vision and growth (Selmi et al 2008).…”
Section: Tbp Physico-chemical Characterizationmentioning
confidence: 99%
See 1 more Smart Citation